2007
DOI: 10.1016/j.gloplacha.2006.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the space and time evolution of equilibrium-line altitudes on Andean glaciers (10°N–55°S)

Abstract: A previous study of Fox [Fox, A.N. 1993. Snowline altitude and climate at present and during the Last Pleistocene Glacial Maximum in the Central Andes (5°-28°S). Ph.D. Thesis. Cornell University.] showed that for a fixed 0°C isotherm altitude, the equilibrium-line altitude (ELA) of the Peruvian and Bolivian glaciers from 5 to 20°S can be expressed based on a log-normal expression of local mid-annual rainfall amount (P). In order to extrapolate the function to the whole Andes (10°N to 55°S) a local 0°C isotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 20 publications
3
73
0
Order By: Relevance
“…In addition the coupling between largescale climatic information, derived from historical simulations or future projections of climate change, and glaciologic and hydrologic models requires downscaling of the climate information to the catchment scale to bridge this scale mismatch. Some studies have circumvented this problem by general approximations of temperature focusing on the close coupling between the ELA of tropical glaciers and the 0°C isotherm (the freezing level) (Condom et al, 2007;Rabatel et al, 2012;Sagredo et al, 2014), while others have exploited the relationship between freezing level height (FLH) and glacier extent . As shown in Fig.…”
Section: Glaciologic Projectionsmentioning
confidence: 99%
“…In addition the coupling between largescale climatic information, derived from historical simulations or future projections of climate change, and glaciologic and hydrologic models requires downscaling of the climate information to the catchment scale to bridge this scale mismatch. Some studies have circumvented this problem by general approximations of temperature focusing on the close coupling between the ELA of tropical glaciers and the 0°C isotherm (the freezing level) (Condom et al, 2007;Rabatel et al, 2012;Sagredo et al, 2014), while others have exploited the relationship between freezing level height (FLH) and glacier extent . As shown in Fig.…”
Section: Glaciologic Projectionsmentioning
confidence: 99%
“…Most of these large remote glaciers are valley glaciers with compound basins that terminate at elevations as low as 1000 m. Rivera et al (2012) have found glaciers in this region that reach minimum elevations as low as 550 m a.s.l. Although no local meteorological information is available for most of these glaciers, there have been a few attempts (Condom et al, 2007;Carrasco et al, 2005 and to constrain the climatic Equilibrium Line Altitude (ELA) at a regional scale based on meteorological data from low altitude stations and scarce mass balance data (Rivera et al, 2006). These studies indicate that the climatic ELA in the region is around 1400 and 2000 m, suggesting that the abundant precipitation of the area would result in an ELA below the 0 • C isotherm.…”
Section: Study Areamentioning
confidence: 99%
“…The mean annual temperature at the Condoriri s tation located at 4490 meters above sea level (masl) is 3.3 °C. According to other studies, the temperature decreases with elevation at a r ate o f 0.7 °C ev ery 100 v ertical m eters 7) . T he relative h umidity cl early r eflects the seasonality.…”
Section: Study Areamentioning
confidence: 80%